The Influence Of Price, Brand Image, And Product Quality Of Ventela Shoes On Purchase Decision Among Students Of The .Faculty Of Economics And Business, Malikussaleh University. - Zikra Bunga Afsara; Sapna Biby; Jullimursyida (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of price, brand image, and product quality on the purchase decision of Ventela shoes (a study on students of the Faculty of Economics and Business, Malikussaleh University). The independent variables in this research are price, brand image, and product quality, while the dependent variable is purchase decision. Primary data were obtained through questionnaires distributed to students who had purchased Ventela shoes. The sampling technique used was incidental sampling. The data analysis method employed was multiple linear regression. The results showed that partially, brand image and product quality have a positive and significant effect on purchase decisions, while price does not have a significant effect. Simultaneously, the three independent variables have a significant influence on the purchase decision of Ventela shoes. This study contributes to a better understanding of the key factors influencing consumer buying behavior toward local products and serves as a useful reference for companies in evaluating their marketing strategies.